Adaptasi pendidikan di era teknologi - Maulana, Najma (Maliki Interdisciplinary Journal, 2024)
In the digital era, the advancement of information and communication technology (ICT) has brought significant changes to the field of education. The learning paradigm has shifted from traditional models to more open and interconnected models, supported by internet devices, educational applications, and online platforms. This transformation has made education more interactive, emphasizing the importance of digital skills to meet contemporary needs. However, these changes also present challenges, such as the need to adjust curricula to prepare future generations for changes in the job market and address technology access disparities. Collaborative learning approaches and constructivist theory provide important foundations for transforming education in the digital era. Technology plays a crucial role in supporting student-centered learning, enhancing social interaction, and developing critical thinking skills. Technology has now become a vital component of education, influencing curricula, student experiences, and problem-solving methods within the educational landscape. By effectively utilizing technology, education in the digital era can create responsive learning environments and prepare students with relevant skills to face future challenges.